Analisis Tanggung Jawab Pelaksanaan Praktik Pengalaman Lapangan (PPL) Mahasiswa STPKat di Santo Fransiskus Asisi Semarang - Gregorius Daru Wijoyoko; Andarweni Astuti (Perkumpulan Perguruan Tinggi Agama Katolik Indonesia, 2022)
This research explored the issue of Internship Study. There were seven participants in this research. Internship Study in the Undergraduate Catholic Education and Teaching program is one of the efforts that provides opportunities for students to strengthen and mature their potential as prospective professional religious teachers. Internship Study is one of the compulsory courses to complete and apply the knowledge already possessed to be applied in the school environment. With this Internship Study, students get real experience that can be used as a basis for self-development to prepare as prospective Catholic Teacher who are aware of their duties and responsibilities as academic staff in the world of education. The first purpose of this study was to find out the process of students becoming responsible or irresponsible in online Internship Study teaching activities. The second objective was to determine the factors that determined the success or failure of online Internship Study teaching activities produced by STPKat Semarang students. The research method was a qualitative case study method. The researcher acted as a living witness of the responsible behavior pattern of the research subject. The research revealed four things. Firstly, maturity was the main factor in defining online PPL responsibilities. Secondly, spirituality of faith was an important factor in online PPL responsibilities. Thirdly, commitment to actively participate in online PPL both from the teacher and students was an important factor in the success of PPL responsibilities. Fourthly, interaction Ecological aspects both from the micro-meso-exo-macrosystem were important factors in the success of online Internship Study.